2015
DOI: 10.1111/jcmm.12673
|View full text |Cite
|
Sign up to set email alerts
|

In vitro expression of cytokeratin 18, 19 and tube formation of adipose‐derived stem cells induced by the breast epithelial cell line HBL‐100

Abstract: Fat transplantation is increasingly used in breast augmentation; and recently, the issue of safety concerns from a cellular and molecular point of view has been raised. In this study, attentions were paid to the interaction between adipose‐derived stem cells (ADSC) and mammary epithelial cells: human breast cancer cell line ‐ 100 (HBL ‐ 100) cells were used to simulate the normal microenvironment in breast tissue, ADSCs were harvest from human and co‐cultured with HBL‐100 cells. It was found that ADSCs formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
11
0
3
Order By: Relevance
“…Cell cytokeratin (CK) is a main cytoskeletal protein in the keratinocyte that is mainly distributed in the epithelial cells, maintaining the integrity and continuity of the epithelial tissue is the major function of such type of structural protein [ 11 , 12 ]. Studies have found that CK is highly conserved and differentiated, closely related to the proliferation and differentiation of epithelial cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cell cytokeratin (CK) is a main cytoskeletal protein in the keratinocyte that is mainly distributed in the epithelial cells, maintaining the integrity and continuity of the epithelial tissue is the major function of such type of structural protein [ 11 , 12 ]. Studies have found that CK is highly conserved and differentiated, closely related to the proliferation and differentiation of epithelial cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…HIF is activated as a result of a drop in pO 2 [24]. Cytokeratin (CK) is a marker for epithelial cells [25, 26]. The intestinal epithelial cells play an important critical role in the immune response within the intestinal tissue and they are involved in the responses to hypoxic situation [27].…”
Section: Introductionmentioning
confidence: 99%
“…Aufgrund ihrer Multipotenz, d. h. ihrer Differenzierungsfähigkeit in unterschiedliche Zelllinien, gelten sie als potente Kandidaten für eine Vielzahl von Anwendungen in der Regenerativen Medizin, wie u. a. im Knochen [51] oder Muskel Tissue Engineering [52]. Weiterhin können sie für die Hautgewebszüchtung eingesetzt werden [53] und können durch die Kokultivierung mit Mammaepithelzellen epithelial differenziert werden [54].…”
Section: Diskussionunclassified